Gender identity and the career decision-making process in matriculants - Seabi, Joseph (South African Journal of Higher Education, 2016)
The purpose of this study was to investigate whether there was a relationship between the gender identity formation and career decision-making process of Grade 12 learners. It was also investigated whether there were any differences between the boys and girls in the study in respect of identity formation and the career decision-making process. Of the 156 learners who participated in the study, 60 were boys and 96 were girls. The Revised Extended Objective Measure of Ego Identity Status and the Study Choice Task Inventory were administered to the learners. The findings revealed a negative correlation between diffusion and foreclosure identity statuses and exploratory behaviour thereby suggesting that identity-diffused and foreclosed adolescents tend to meander and drift aimlessly without actively engaging in career exploration. No gender differences were found in identity formation and the career decision-making process implying that, unlike in the past, the girls considered stereotypical female as well as stereotypical male paths of career development.